TEACHERS STRATEGIES IN TEACHING SPEAKING AT SMK NEGERI 1 KOTA TERNATE - Indriyani Amir; Fitria Wulan Sari; Anwar Ismail (FKIP Universitas Khairun, 2022)
The objective of this research was to determine the teachers strategies used in teaching speaking. This research took place at SMK Negeri 1 Kota Ternate. This research used a qualitative descriptive method to describe the teachers strategy in teaching speaking. The subjects in this research were 3 English Teachers at SMK Negeri 1 Kota Ternate in classes X and XI, 2 teachers from class X, and 1 teacher from class XI. The data were collected by classroom observation, interview, and documentation. The result of this research showed that every teacher used a strategy in teaching speaking according to the teaching material, classroom environment, and student needs. The strategies that are often used by teachers at SMK Negeri 1 Kota Ternate are live listening, task repetition, presentation and talks, discussion, and conversations and chats. While the strategies that are rarely used are recording and transcripts, noticing-gap-activity, drilling and chanting, writing tasks, and debates and for the unused strategy are stories, jokes, anecdotes, drama, role-play, and simulation, and speaking outside class.